2020
DOI: 10.1111/his.14090
|View full text |Cite
|
Sign up to set email alerts
|

Post‐radiotherapy vascular lesions of the breast: immunohistochemical and molecular features of 74 cases with long‐term follow‐up and literature review

Abstract: Aims A wide range of post‐radiotherapy (RT) vascular lesions can occur, ranging from benign lymphangiomatous papules of the skin (BLAPs), to atypical vascular lesions (AVLs) and post‐RT angiosarcomas (ASs). The relationship between benign and malignant post‐RT breast lesions and their prognostic features are still controversial. The aims of this study were to investigate the relationship between benign and malignant mammary post‐RT vascular lesions and to define post‐RT AS prognostic features. Methods and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Grading of RT-AS is controversial and not consistently reported, given the discrepant results regarding its prognostic value. 9,[22][23][24] Recently, two studies have shown that histological grade 3 RT-ASs of the breast are associated with worse OS and DFS than grade 1 or 2 tumours. 9,23 In a study of 176 radiation sarcomas (including 67 RT-ASs of the breast), Mito et al found that high-grade tumours were associated with worse OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grading of RT-AS is controversial and not consistently reported, given the discrepant results regarding its prognostic value. 9,[22][23][24] Recently, two studies have shown that histological grade 3 RT-ASs of the breast are associated with worse OS and DFS than grade 1 or 2 tumours. 9,23 In a study of 176 radiation sarcomas (including 67 RT-ASs of the breast), Mito et al found that high-grade tumours were associated with worse OS.…”
Section: Discussionmentioning
confidence: 99%
“…9,[22][23][24] Recently, two studies have shown that histological grade 3 RT-ASs of the breast are associated with worse OS and DFS than grade 1 or 2 tumours. 9,23 In a study of 176 radiation sarcomas (including 67 RT-ASs of the breast), Mito et al found that high-grade tumours were associated with worse OS. 25 On the basis of these findings, reporting the histological grade of RT-AS is recommended, as it may have prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of primary and secondary angiosarcomas have found conflicting results on the prognostic significance of tumor size and margin status. 4,5,14,17,[21][22][23][24][25] Similarly, other studies have not found a predictive value in adjuvant/neoadjuvant therapy. 2,21 It should be noted that histologic grading should be reserved for excision specimens.…”
Section: Discussionmentioning
confidence: 99%
“…112 Majority of PTEN mutation reported to the AS Project were putative drivers, including truncating and missense mutations, with only one patient harbouring missense mutation of unknown significance 113 (detailed explanation in Figures 2 and 3). Corradini et al 114 identified PTEN mutants in 50% in radiotherapy-induced ASs. 114 Studies showed that AS has weak PTEN immunoreactivity, 115 and in high-grade tumours PTEN expression was largely absent.…”
Section: Alterations Of Intracellular Signalling Pathways and Importa...mentioning
confidence: 99%